A comparison of supracostal and infracostal access approaches in treating renal and upper ureteral stones using MPCNL with the aid of a patented system. Issue 1 (December 2015) - Fan, Difu; Song, Leming; Xie, Donghua; Hu, Min; Peng, Zuofeng; Liao, Xiaohui; Liu, Tairong; Du, Chuance; Zhu, Lunfeng; Yao, Lei; Huang, Jianrong; Yang, Zhongsheng; et al.
Abstract Background There are still disagreements on which is a better approach to choose to establish percutaneous tract for percutaneous nephrolitotomy (PCNL), between supracostal and infracostal approaches. The aim of this study is to investigate the safety, efficacy and practicability of minimally invasive PCNL (MPCNL) with the aid of a patented system either through supracostal or through infracostal access. Methods A retrospective study was carried out for 83 patients with renal or upper ureteral stones. Under the guidance of B ultrasound or C-arm, these patients were treated by MPCNL through either 12th rib infracostal (Group 1, 43 cases) or supracostal (Group 2, 40 cases) access approach. These 2 groups were compared for total number of percutaneous tracts, average time in establishing a given percutaneous tract, the number of percutaneous tract used for each case, the average stone clearance time, the clearance rate of all stones by one surgery, and the amount of bleeding using a single percutaneous tract. Results There was a significantly smaller total number of percutaneous tracts needed, a smaller number of cases that needed two percutaneous tracts to clear stones completely, a shorter average time in establishing a percutaneous tract, and a smaller average amount of bleeding in infracostal access group. At the same time, there were a significantly larger number of cases in which stones were cleared completely using a single percutaneous tract and a higher renal stone clearance rate by one surgery. Conclusion There were several advantages of infracostal access. These included accuracy in establishing a percutaneous tract, safety, quickness, convenience and flexibility in moving the patented sheath, and higher renal and upper ureteral stone clearance rate by one surgery.